Towards an Effective Communication in Kenyan Long-Term Disease Patients’ Care via Cybernetic- A Systematic Review - Christopher Oyuech Otieno; Martha W. Kiarie Makara; Naomi N. James; Grace Mbogo Liyai (Science and Technology: Recent Updates and Future Prospects Vol. 9, 2024)
In this paper, to effectively treat chronic disorders and improve the standard of care, effective communication between patients and healthcare professionals is essential. The aim of the study was to review the literature on how good communication might improve treatment outcomes for Kenyan patients with chronic and terminal illnesses and to determine whether Cybernetic electronic communication can improve those outcomes even more. The word Cybernetics comes from the Greek word, kybernetes, meaning rudder, pilot, a device used to steer a boat or to support human governance. Cybernetics is concerned with concepts at the core of understanding complex systems such as learning, cognition, adaptation, emergence, communication, and efficiency. We uncovered the history of treatment outcomes for chronic and terminal dis-eases in this research study, both with and without communication at the core of the patient’s care plan. We discussed the importance of good communication in the treatment of patients with chronic and terminal illnesses and why it is a momentous endeavor comparable to medical diagnosis and treatment for the long-term health of patients. To locate pertinent material for the background literature study, we carried out a comprehensive literature search. Although the preliminary literature review was a continuation of the introduction research, it also highlighted the paucity of local Kenyan literature and suggested that improved communication might help patients with chronic and terminal illnesses have better treatment outcomes. Methodology maintained the literature search, as a systematic literature review focused on the core of the study, making separate sections of the same body necessary. This ensured that a methodological literature search section is as comprehensive as possible. We used an integrated PRISM model to limit a comprehensive literature search and a systematic literature review design as part of the overall process. Non-probability sampling and snowball approaches on literary pa-pers over the previous 17 years were used in this arrangement. Since this was a multidisciplinary study, the four experts who also serve as authors were chosen from within their respective fields of expertise to design the study. They created search strategies, generated key words, looked up keywords in database engines, assessed the results of the literature using the PRISMA logical model, looked over successful literature, and triangulated their findings. The conclusions of the experts individually revealed a convergence of thoughts, beliefs, and practices. The study concluded that even though there isn’t much research done in Kenya on the same subject; what is available illustrates how crucial good communication is for patients with chronic illnesses. The study’s findings also highlighted the positive effects of effective communication between patients and healthcare professionals on treatment plan adherence, patient satisfaction, and overall health outcomes. The findings stated that to ensure truly effective communication at the center of care to patients with long-term disease, then adoption and integration of Cybernetics is supreme. The results also noted that in order to improve patient care and outcomes, Kenyan healthcare workers should underscore developing their communication skills. The study also found that the incorporation of cybernetics is crucial if truly effective communication is required so as to enable centered care for patients with long-term diseases in Kenya. The goal of Cybernetics is to activate genuinely effective communication in the care of Patients with long-term disease in Kenya. This study is organized by beginning with an abstract, followed by keywords, an introduction, literature review, methodology, findings, discussion, and finally conclusions.